2021
DOI: 10.3390/s21144935
|View full text |Cite
|
Sign up to set email alerts
|

Secure and Efficient High Throughput Medium Access Control for Vehicular Ad-Hoc Network

Abstract: The evolution of the internet has led to the growth of smart application requirements on the go in the vehicular ad hoc network (VANET). (VANET) enables vehicles to communicate smartly among themselves wirelessly. Increasing usage of wireless technology induces many security vulnerabilities. Therefore, effective security and authentication mechanism is needed to prevent an intruder. However, authentication may breach user privacy such as location or identity. Cryptography-based approach aids in preserving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Dual‐channel transmission involving control and service channels is used by the protocol to ensure service performance that is sensitive to certain delays [16]. A quick overview of current technologies, standardization, and existing technology capabilities is presented in [17].…”
Section: Related Workmentioning
confidence: 99%
“…Dual‐channel transmission involving control and service channels is used by the protocol to ensure service performance that is sensitive to certain delays [16]. A quick overview of current technologies, standardization, and existing technology capabilities is presented in [17].…”
Section: Related Workmentioning
confidence: 99%
“…Al et al’s work [ 219 ] shows secure performed enriched channel allocation, i.e., shared channel, using commutative RSA (CRSA) [ 220 ]. In the CRSA scheme, two prime numbers are required to be sent to all vehicles using random number encryption and decryption parameters, which will be generated, and it is required to exchange keys to each vehicle.…”
Section: Iot Security Solutionsmentioning
confidence: 99%
“…Therefore, balancing block size and security has proven to be a difficult task. Second, it has been demonstrated that selfish mining tactics can result in miners earning more money than is reasonable for them [8]. To generate more money in the future, miners conceal their extracted blocks.…”
Section: Related Workmentioning
confidence: 99%